2021
DOI: 10.1111/jpm.12757
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with use of coercive practices in adult mental health inpatients: A systematic review

Abstract: What is known on the subject?• Coercive practices such as restraint (physically holding a person) or seclusion (containing a person in locked room) are frequently used in mental health care.• How often and which specific practices are used is not consistent across different healthcare systems, hospitals or wards.• Internationally, there is agreement on the need to monitor and reduce the use of coercive practices. What this paper adds to existing knowledge?• The reviewed evidence suggests a number of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 78 publications
0
38
0
1
Order By: Relevance
“…Ethnic minorities were significantly more likely to receive seclusion in all but one study, where the inverse association was reported [ 79 ]. However, after adjusted analysis, the reverse association was reported in one further study [ 68 ], whereas associations became non-significant in three studies [ 7 , 59 , 62 ]. In Western Pacific-based studies, ethnic minorities were indigenous (e.g.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Ethnic minorities were significantly more likely to receive seclusion in all but one study, where the inverse association was reported [ 79 ]. However, after adjusted analysis, the reverse association was reported in one further study [ 68 ], whereas associations became non-significant in three studies [ 7 , 59 , 62 ]. In Western Pacific-based studies, ethnic minorities were indigenous (e.g.…”
Section: Resultsmentioning
confidence: 90%
“…Three studies reported significant associations between ethnicity and rapid tranquillisation [ 7 , 39 , 77 ], of which there was no further description in one study [ 77 ]. Ethnic minorities, in this case people of foreign citizenship (Swiss-based study) or not further described (review study), were significantly more likely to receive rapid tranquillisation in the two remaining studies [ 7 , 39 ]. However, these associations became non-significant after using adjusted analysis, although, proportionally, ethnic minorities were more likely to receive rapid tranquillisation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations